STUDI KOMPARASI PEMAKAIAN GPS METODE REAL TIME KINEMATIC (RTK) DENGAN TOTAL STATION (TS) UNTUK PENENTUAN POSISI HORISONTAL - Fajriyanto Fajriyanto (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2009)
Measurement of control point by conventional method often given on to some obstacle especiallyrelated to low measurement efficiency and speed, strength of figure and spreading point controlvery suspended condition of field. According to growth and progress of technology with existenceof satellite of GPS have watered down work of geodesy with result of able to be pledged. As systemdetermination of position have satellite bases of GPS very useful in determination of geodeticalposition for the work of mapping and survey. Research conducted by using Total Station TopconGTS-2R and receiver GPS Leica System 300 at polygon network closed which consist of six pointswith one of point as reference station, data processing use SKI software and Microsoft office forthe calculation of polygon by using method bowdith flattening and flattening program TurboPascal. Result of from this research be based to value of confidence region that smaller ellipsvalue mistake from point hence progressively check made polygon network. By using conventionalmethod in the reality more is coming near of order II than GPS method of Real Time Kinematic (RTK). Yielded by Precise Mean GPS method of RTK equal to 0.009 metre, obtained accuration0.0965 correctness and metre relative to conventional method is 0.106 metre. In general alllocated measured points outside ellips standard error at trust 95 %.